2016
DOI: 10.1017/s0007485316000882
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, expression analysis and RNAi knock-down of elongation factor 1α and 1γ fromNilaparvata lugens and its yeast-like symbiont

Abstract: In the present paper, four cDNAs encoding the alpha and gamma subunits of elongation factor 1 (EF-1) were cloned and sequenced from Nilaparvata lugens, named NlEF-1α, NlEF-1γ, and its yeast-like symbiont (YLS), named YsEF-1α and YsEF-1γ, respectively. Comparisons with sequences from other species indicated a greater conservation for EF-1α than for EF-1γ. NlEF-1α has two identical copies. The deduced amino acid sequence homology of NlEF-1α and NlEF-1γ is 96 and 64%, respectively, compared with Homalodisca vitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The main function of EF-1γ is to ensure the correct scaffolding of different subunits in the EF-1 complex as well as to direct its intracellular localization [43]. The expression stability of EF-1γ had previously been evaluated in P. ginseng [34] and Nilaparvata lugens [44]. In our study, EF-1γ was one of the two most suitable reference genes with stable expression levels under various experimental conditions.…”
Section: Discussionmentioning
confidence: 84%
“…The main function of EF-1γ is to ensure the correct scaffolding of different subunits in the EF-1 complex as well as to direct its intracellular localization [43]. The expression stability of EF-1γ had previously been evaluated in P. ginseng [34] and Nilaparvata lugens [44]. In our study, EF-1γ was one of the two most suitable reference genes with stable expression levels under various experimental conditions.…”
Section: Discussionmentioning
confidence: 84%
“…IDGFs were confirmed to be the proteins cooperating with insulin that promote cell lineages derived from imaginal discs in Drosophila melanogaster (Kawamura et al, 1999;Varela et al, 2002;Zurovcová and Ayala, 2002). RNAi has been widely used to find out the functions of vital genes in different insects of economic importance (Tomoyasu and Denell, 2004;Chen et al, 2008;Gong et al, 2012;Asokan et al, 2013;Zhang et al, 2013;Qi et al, 2015;Wang et al, 2017;Ullah et al, 2020a). Recently, a study reported that silencing of IDGF6 in Bactrocera correcta through RNAi significantly decreases the expression of IDGF6, causes larval mortality and wing malformation in adult flies (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi) is widely used to study gene function by suppressing gene expression via the injection of dsRNA (Fire et al , 1998). RNAi technology also has been widely used to investigate the functions of essential genes in insects (Tomoyasu & Denell, 2004; Chen et al ., 2008; Gong et al ., 2012; Wang et al ., 2017; Zhang et al ., 2013; Asokan et al ., 2013; Qi et al ., 2015), and has been particularly employed to silence vital genes (Belles, 2010; Liu et al , 2010; Wang et al , 2012). Similar studies using RNAi have resulted in diverse malformed phenotypes in insects and show varying efficiencies in the insect tissues investigated (Zhu et al , 2008; Belles, 2010; Scott et al , 2013; Xi et al , 2015).…”
Section: Introductionmentioning
confidence: 99%